Farmer Empowerment in Improving Beef Cattle Farming Business in Tonsewer Village, Regency Minahasa - Lenzun, Gam D.; Lainawa, Jolyanis; Tumewu, Judy. M. (AIBPM Publisher, 2023)
The research objective was to examine the relationship between social engineering, economic engineering, technological engineering and value-added engineering with beef cattle business development in Tonsewer Village, West Tompaso District, Minahasa Regency based on farmers' perceptions. The analysis found that there is a significant relationship between the engineering variables and the variable of beef cattle business improvement. The level of relationship strength falls into the